Características estadísticas del índice general de la Bolsa de Valores de Colombia (IGBC) en sus primeros 10 años - Alonso, Julio César (2014)
There are many studies published in the literature on stylized facts in financial time series. However, for the Colombian case there is only one work that documents the stylized facts of the returns. Alonso and Arcos (2006) documented the presence of four stylized facts in the exchange rate series and the principal Colombian Stock Exchange Index (IGBC), using a daily sample for the period from January 21, 1999 to April 31, 2005. The aim of this document is to present five stylized facts on the behavior of the IGBC returns in its first 10 years. Furthermore, a wider range of statistical test is used to support the existence of those stylized facts. Evidence is provided for the following stylized facts: I) no efficiency of the market; II) heavy tails of the distribution; III) aggregational Gaussianity; IV) volatility clustering and V) Taylor effect. In our case, the sample of the daily IGBC will be used for the period between July 3, 2001 and July 5, 2011.